2008
DOI: 10.1177/1076029607303963
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Management of an Aneurysmal Subarachnoid Hemorrhage in a Patient With Known Factor XI Deficiency: A Case Report

Abstract: The authors report a rare case of an acute cerebral aneurysm rupture in a patient with a known factor XI deficiency. Aneurysmal subarachnoid hemorrhage (SAH) accounts for a high mortality and morbidity rate. When SAH is associated with an inherited coagulation disorder such as hemophilia C, an unexpected and possible increase in hemorrhagic stroke and increase in bleeding during surgery and in the postoperative period could lead to an extremely bad outcome. Clinical management consists of rapid correction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The current study examined prolonged prothrombin duration as one of the independent prognostic factors for ICH in patients with hematological malignancies. Leukemic cells may express fibrinolysis and other proteolysis enzymes, which has been implicated in the pathogenesis of bleeding in some patients [38-40]. Chemotherapy-related endothelial injury and reduction of coagulation factors also could play a role in the pathogenesis [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The current study examined prolonged prothrombin duration as one of the independent prognostic factors for ICH in patients with hematological malignancies. Leukemic cells may express fibrinolysis and other proteolysis enzymes, which has been implicated in the pathogenesis of bleeding in some patients [38-40]. Chemotherapy-related endothelial injury and reduction of coagulation factors also could play a role in the pathogenesis [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…An optimal therapeutic strategy when one suffers from unanticipated bleeding is the administration of human FXI concentrate (HFC) [7]. However, infusion of HFC should be approached with caution, because fatal thrombosis events have been reported in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, infusion of HFC should be approached with caution, because fatal thrombosis events have been reported in some cases. Siao et al [7] reported the administration of HCF under strict monitoring to maintain the target concentration, which required a multidisciplinary approach. Furthermore, in some countries, including Japan, FXI concentrate is not commercially available or licensed for use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations